Recent Research on Energy Efficient Clustering Based Secured Multihop Routing Protocols in MANET - Dr. P. Kiran Kumar, Dr. M. V. S. S. Nagendranath (Mathematical Statistician and Engineering Applications, 2022)
This article provides a comprehensive review of different techniques related to the proposed models available in the literature. It depicts a concise survey of distinct energy efficient clustering approaches in MANET. Next, a brief survey of various routing techniques has been discussed, including classical and recently proposed techniques. Besides, an elaborate survey of diverse energy aware routing techniques in MANET is explained. Along with that, the trust-based schemes are also discussed briefly. Followed by, security enhancement techniques have been elaborated. Moreover, an extensive comparison of the reviewed techniques has also been made in this article.